2006
DOI: 10.3171/jns.2006.105.5.675
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of muscle motor evoked potentials during cerebral aneurysm surgery: intraoperative changes and postoperative outcome

Abstract: Data in this study demonstrated that MMEPs are a useful means of intraoperative neurophysiological monitoring of motor pathway integrity and predicting postoperative motor status. The intraoperative loss of MMEPs reliably predicts both severe and permanent postoperative motor deficits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(104 citation statements)
references
References 26 publications
2
95
0
7
Order By: Relevance
“…Use of MEP monitoring in intracranial neurovascular surgery is often avoided because of concern for unacceptable movement in a nonparalyzed patient (26,29). It was previously reported that in approximately 6%e10% of patients undergoing transcranial MEP monitoring without neuromuscular blockade, recording was impossible during microsurgery because of electrostimulation-induced muscle contraction or failure to elicit a baseline motor response from muscles that were intact in the preoperative period (20,27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of MEP monitoring in intracranial neurovascular surgery is often avoided because of concern for unacceptable movement in a nonparalyzed patient (26,29). It was previously reported that in approximately 6%e10% of patients undergoing transcranial MEP monitoring without neuromuscular blockade, recording was impossible during microsurgery because of electrostimulation-induced muscle contraction or failure to elicit a baseline motor response from muscles that were intact in the preoperative period (20,27).…”
Section: Discussionmentioning
confidence: 99%
“…It has even been suggested that with MEP monitoring the incidence of motor deficits after aneurysm clipping could be reduced to at least the level obtained with aneurysm coiling procedures (31). However, MEPs in intracranial neurovascular surgery have often not been employed because of concern for unacceptable movement in a nonparalyzed patient anesthetized with a limited amount, or in the absence, of inhaled volatile anesthetic (26,29). A survey sent to all members of the American Society of Neurophysiological Monitoring and the American Clinical Neurophysiology Society revealed that only two centers used MEPs during craniotomies for intracranial lesions (from -OBJECTIVE: To review the experience at a single institution with motor evoked potential (MEP) monitoring during intracranial aneurysm surgery to determine the incidence of unacceptable movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In intramedullary spinal cord tumor surgery, total MEP loss was shown to be a valid warning criterion. [5] For supratentorial surgery, a 50% reduction of MEP response amplitude has been proposed as a warning criterion [10,11,17].…”
Section: Mep Warning Criteria In Spinal and Supratentorial Surgerymentioning
confidence: 99%
“…Although MEPs are well established for the early detection of impending motor deficit during surgery of cranial procedures [10,11,14,17,19] and the spinal cord [1,5,15,16], for brainstem surgery a warning criterion has not yet become generally accepted.…”
Section: Introductionmentioning
confidence: 99%